(untitled) (Journal of the College of Basic Education, 2025)
There are some difficulties that some students encounter when solving verbal problems. Perhaps the most important of them is the students’ weakness in the reading ability of mathematical problems and thus the difficulty of understanding and comprehending them. This is what some research has indicated, so these researches have recommended the importance of reading in facilitating the solution of verbal problems in mathematics.To verify this, the researcher decided to conduct a study whose goal was to verify the existence of a relationship between mathematical reading ability and problem solving. Verbal among primary school students.A null hypothesis was developed in order to verify the aim of the study. ((There is no relationship between mathematical reading ability and solving verbal problems among fourth-primary students))To verify the hypothesis, the researcher needed to prepare two tests, one for mathematical reading ability and the other for verbal problems. The researcher chose fourth-grade primary school students from schools belonging to the Baghdad Education Directorate/Al-Karkh III/Kadhimiya District for the academic year 2021-2022 AD to be the research population. The sample consisted of 200 male and female students from the class. Fourth primary school. The descriptive approach was the approved approach. The researcher prepared two research tools: the mathematical reading ability test, which consisted of 20 items, and the silver issues test, which consisted of 10 items. To verify the research hypothesis, the researcher used some statistical methods, namely: (the difficulty factor and the distinction factor (for the essay and thematic items)) The Cronbach-Alpha stability equation, the Kuder-Richard stability equation, the effectiveness of alternatives equation, and the Pearson correlation coefficient, Weight percentile, z test ) After conducting two tests on the sample, correcting the papers, and performing statistical analyses, the following result was reached:(Rejecting the null hypothesis) That is, the study proved that there is a relationship between mathematical reading ability and solving verbal problems among the research sample.In light of the results, the researcher made recommendations including :Providing mathematics teachers, both male and female, with some reading strategies and skills, and developing training programs for them to apply these strategies in solving verbal problems, and taking into account the student’s age and his environmental and cultural level when formulating verbal problems and reviewing them by specialists in the Arabic language.